2011
DOI: 10.1017/s0007114511001875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary water intake on urinary output, specific gravity and relative supersaturation for calcium oxalate and struvite in the cat

Abstract: It has been reported that daily fluid intake influences urinary dilution, and consequently the risk of urolithiasis in human subjects and dogs. The aim of the present study was to investigate the role of dietary moisture on urinary parameters in healthy adult cats by comparing nutritionally standardised diets, varying only in moisture content. A total of six cats were fed a complete dry food (6·3 % moisture) hydrated to 25·4, 53·2 and 73·3 % moisture for 3 weeks in a randomised block cross-over design. Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 9 publications
3
51
1
5
Order By: Relevance
“…In the study of Buckley et al . ( 16 ) a 73·7 % moisture diet was fed and drinking water intake was 30 ml/kg BW per d; for the present study this was 0·17 ml/kg BW per d when the wet diet was fed and 0·88 ml/kg BW per d when the dry with added water diet was fed. It appears that the higher moisture content of the canned diet in the present study (82 %) provided the great majority of the cats’ requirements.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the study of Buckley et al . ( 16 ) a 73·7 % moisture diet was fed and drinking water intake was 30 ml/kg BW per d; for the present study this was 0·17 ml/kg BW per d when the wet diet was fed and 0·88 ml/kg BW per d when the dry with added water diet was fed. It appears that the higher moisture content of the canned diet in the present study (82 %) provided the great majority of the cats’ requirements.…”
Section: Discussionmentioning
confidence: 66%
“…In the study of Buckley et al . ( 16 ) a dry diet was hydrated with water to obtain four dietary treatments with moisture levels of 6·3, 25·4, 53·2 and 73·3 %. Water intake increased when dietary moisture level increased.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this meta-analysis confirmed the effectiveness of fluid therapy for primary and recurrent stone prevention. Although the type of fluid intake in most studies was not clearly defined [10,11,1317], both increased water intake [26] and increased general fluid intake [27] resulted in higher urine output. A number of studies [11,12,15] in this meta-analysis demonstrated that high fluid consumption to achieve a minimum urine volume of 2.0–2.5 L/d (as recommended by AUA and ACP guidelines [5,6]) significantly reduced the risk of incident and recurrent kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Independente de quaisquer outras alterações predisponentes à urolitíase que possam estar presentes, o fator predisponente primordial e necessário para a formação de todos os tipos de cálculos urinários é a supersaturação urinária por substâncias cristalogênicas (OSBORNE et al, 1995;NEUHAUS et al, 2000;KOEHLER et al, 2008;ULRICH et al, 2008;BUCKLEY et al, 2011;OKAFOR et al, 2014). Desse modo, a produção de urina concentrada e com altos níveis de minerais calculogênicos é o fator de risco mais importante para o desenvolvimento dos urólitos (BUCKLEY et al, 2011).…”
Section: Supersaturação Urináriaunclassified
“…Desse modo, a produção de urina concentrada e com altos níveis de minerais calculogênicos é o fator de risco mais importante para o desenvolvimento dos urólitos (BUCKLEY et al, 2011).…”
Section: Supersaturação Urináriaunclassified